2010
DOI: 10.1007/s00438-010-0542-7
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and transcriptomic characterization of a virulence-deficient phosphatidylcholine-negative Agrobacterium tumefaciens mutant

Abstract: Phosphatidylcholine (PC) is the most abundant phospholipid in eukaryotic membranes, whereas only a limited number of bacteria are able to synthesize PC. Intriguingly, many of the bacteria with PC-containing membranes interact with eukaryotic hosts. PC is one of the major membrane lipids in the phytopathogenic bacterium Agrobacterium tumefaciens. The presence of PC is critical for diverse cellular processes like motility, biofilm formation, stress resistance, and virulence. The exact role of PC in these process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 59 publications
2
30
0
Order By: Relevance
“…Other vir operons, such as virB , virC and virD were only expressed under induction condition. These vir genes expression patterns were consistent with previous microarray and RNA-seq studies (Table S1 in File S1) [38], [51].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Other vir operons, such as virB , virC and virD were only expressed under induction condition. These vir genes expression patterns were consistent with previous microarray and RNA-seq studies (Table S1 in File S1) [38], [51].…”
Section: Resultssupporting
confidence: 91%
“…Several transcriptome analyses using microarrays have identified differentially expressed genes in A. tumefaciens in response to various conditions, such as low pH [36], plant-derived signaling molecules [37], and the loss of phosphatidylcholine biosynthesis [38]. A few recent studies showed that A. tumefaciens uses ncRNAs to regulate important biological processes, such as Ti plasmid replication [39] and the uptake of a plant-derived signaling molecule, γ-amynobutyric acid (GABA) by an ABC transporter [40].…”
Section: Introductionmentioning
confidence: 99%
“…⌬podJ At was created through allelic exchange resulting in a markerless deletion of the Atu0499 open reading frame and the short hypothetical Atu0500 open reading frame that overlaps the 5= end of Atu0499. Transcription of Atu0500, however, was not detected in microarray data, indicating that it is not likely expressed (25). Deletion of podJ At was verified by PCR amplification of the Atu0499 locus and flanking regions from genomic DNA and sequencing of the PCR product.…”
Section: Resultsmentioning
confidence: 99%
“…A subset of the A. tumefaciens LDTs were selected for localization studies to sample the various phylogenetic branches and to test the LDTs that were most highly expressed in transcriptome studies (28). A C-terminal superfolding GFP (sfGFP) (29, 30) fusion to Atu0845, one of the Rhizobiales / Rhodobacterales -specific LDTs, exhibited a striking localization to the growth pole (Fig.…”
Section: Resultsmentioning
confidence: 99%